Global civil society? - Keane, John (Cambridge University, 2013)
ohn Keane tracks the recent development of a powerful big idea - global civil society. Keane explores the jumble of contradictory forces currently nurturing or threatening its growth, and shows how talk of global civil society implies a political vision of a less violent world founded on legally sanctioned power-sharing arrangements among many different and intermingling forms of socio-economic life. Keane's reflections are pitted against the widespread feeling that the world is both too complex or too violent and crazy to deserve serious reflection. His account borrows from various scholarly disciplines, including political science and international relations, to challenge the normative silence and confusion within much of the contemporary literature on globalisation and global governance. Against fears of terrorism, rising tides of xenophobia, and loose talk of 'anti-globalisation', the defence of global civil society mounted here implies the need for new democratic ways of living - and for brand-new democratic thinking about such planetary matters as global markets, uncivil war, university life, and government with a global reach.